2006
DOI: 10.1016/j.jcrysgro.2005.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Impact on structural, optical and electrical properties of CuCl by incorporation of Zn for n-type doping

Abstract: g-CuCl is a wide-band gap (E g ¼ 3:395 eV at 4 K), direct band gap, semiconductor material with a cubic zincblende lattice structure. A very large exciton binding energy (190 meV), assures efficient exciton-based emission at room temperature. Its lattice constant, a CuCl ¼ 0:541 nm means that the lattice mismatch to Si (a Si ¼ 0:543 nm) is o0.5%.g-CuCl on Si-the growth of a wide-band gap, direct band gap, optoelectronics material on silicon substrate is a novel material system, with compatibility to current Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
5
20
0
Order By: Relevance
“…Similar to PL, the peak position is slightly red-shifted compared to the energy of ~3.23 eV measured for undoped CuCl. A broad green emission band centred at ~2.39 eV is consistent with cathodoluminescence (CL) data performed on both undoped [14] and Zn-doped material [6]. Thickness dependent CL spectra have shown that the emission originates in the bulk of the CuCl film [15] and therefore may be related to grain boundaries.…”
Section: DC Looksupporting
confidence: 82%
See 4 more Smart Citations
“…Similar to PL, the peak position is slightly red-shifted compared to the energy of ~3.23 eV measured for undoped CuCl. A broad green emission band centred at ~2.39 eV is consistent with cathodoluminescence (CL) data performed on both undoped [14] and Zn-doped material [6]. Thickness dependent CL spectra have shown that the emission originates in the bulk of the CuCl film [15] and therefore may be related to grain boundaries.…”
Section: DC Looksupporting
confidence: 82%
“…If contact noise is high, as in our case, a noise spike during just one of the eight Van der Pauw measurements can greatly affect the final result. Figure We have previously reported that doping of CuCl by co-evaporation with ZnCl 2 results in the quenching of the excitonic emission one day after deposition measured by UV-VIS spectroscopy and is accompanied by a decrease in the transmittance of the Zn-doped films [6]. For optoelectronic device applications both the electrical conductivity and the optical transmission should be as high as possible [9].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations